2011
DOI: 10.1002/iroh.201011312
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cell Hydrophobicity on Colony Formation in Microcystis (Cyanobacteria)

Abstract: Colony formation is highly import ant for the competitive advantage of the cyanobacterium Microcystis over other phytoplankton species. The laboratory-grown colonial Microcystis strains isolated from Lake Taihu (China) maintained colonial forms under the low light condition (10 μE m ) leaded to the significant decrease in the cell hydrophobicities of the colonial Microcystis and the transition from colonial forms to unicellular forms. These findings indicated that the cell hydrophobicity of Microcystis may pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Moreover, high concentrations of combined N and P caused colonial morphologies of Microcystis to disappear [65]. Other environmental drivers (e.g., temperature, salinity, pH, light, and UVR) [65][66][67] and biotic factors (e.g., grazing, allelopathy, and other interspecific interactions) [68][69][70][71] induce colony formation in cyanobacteria and other phytoplankton. Dominant factors such as nutrient deprivation may drive the formation of colonies.…”
Section: Differential Impacts Of Fe and P Stress On Colony Formation mentioning
confidence: 99%
“…Moreover, high concentrations of combined N and P caused colonial morphologies of Microcystis to disappear [65]. Other environmental drivers (e.g., temperature, salinity, pH, light, and UVR) [65][66][67] and biotic factors (e.g., grazing, allelopathy, and other interspecific interactions) [68][69][70][71] induce colony formation in cyanobacteria and other phytoplankton. Dominant factors such as nutrient deprivation may drive the formation of colonies.…”
Section: Differential Impacts Of Fe and P Stress On Colony Formation mentioning
confidence: 99%
“…Beyond quantitative differences, the mutant exhibited alterations of the EPS hydrophobicity, indicating changes in the chemical composition of the matrix. EPS of Microcystis is involved in colony formation and reacts dynamically in response to environmental stimuli (Beardall et al, 2009;Yamamoto et al, 2011;Yang et al, 2011). Because colony formation is a trait commonly lost in laboratory-cultured Microcystis, we could not suffi-ciently evaluate the impact of MAAs on colony formation and cell-cell recognition in Microcystis.…”
Section: Discussionmentioning
confidence: 99%
“…Uronic acids might mainly contribute to the anionic character of cyanobacterial EPS (Verspagen et al 2006;Klock et al 2007). The hydrophobic interaction could play a key role in the EPS assembly from phytoplankton (Ding et al 2009), and the hydrophobicity of colony was stronger than that of single cell (Yang et al 2011;Liu et al 2016). Yang et al (2011) further specified that the extracellular polysaccharides may play a role in adhering cells together to form colonies.…”
Section: Charge Characteristics and Hydrophobicity Of Cyanobacterial Epsmentioning
confidence: 99%
“…The hydrophobic interaction could play a key role in the EPS assembly from phytoplankton (Ding et al 2009), and the hydrophobicity of colony was stronger than that of single cell (Yang et al 2011;Liu et al 2016). Yang et al (2011) further specified that the extracellular polysaccharides may play a role in adhering cells together to form colonies. Zhang et al (2007) observed that the colonial Microcystis aeruginosa cells have thicker polysaccharides envelope than the unicellular cells.…”
Section: Charge Characteristics and Hydrophobicity Of Cyanobacterial Epsmentioning
confidence: 99%